Rapid Detection of Multidrug-Resistant Mycobacterium tuberculosis by Real-Time PCR based Assay in Indian Population - Jayalakshmi2; D.S. Joshi1*, M. Rathore1, Girish Pai1, T.K. (Recent Research in Science and Technology, 2011)
The current study evaluates a rapid Real-Time Polymerase Chain reaction (RT-PCR) based assay for the detection of Mycobacterium tuberculosis complex (MTC) strains by targeting the IS6110 insertion element. In addition,Ã‚Â hydrolysis probes were used, in this investigation for the diagnosis of Drug Resistance to genotype specific point mutations in rpo B and kat G genes in Mycobacterium tuberculosis that conferÃ‚Â resistance to rifampin (RIF) and isoniazid (INH) respectively,. This assay demonstrated high degree of sensitivity for detection Mycobacterium Tuberculosis. This method provides a rapid, sensitive and robust protocol for diagnosis of Multi Drug Resistant (MDR) MTB and offers several advantages over current molecular and culture-based techniques.